(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Asthma is one of the most common chronic diseases worldwide and has been increasing in prevalence over the last few decades. Magnesium (Mg++) has been shown to relax bronchial smooth muscle and influence the function of respiratory muscles. Hypomagnesemia has been associated with diminished respiratory muscle power. Objective: The purpose of the present study was to assess the serum Mg++ level in bronchial asthma patients during stable state and during exacerbation (Acute severe asthma). Methodology: This comparative cross-sectional study was conducted in the OPD and IPD of Department of Pulmonology at Enam Medical College and Hospital, Savar, Dhaka, Bangladesh and this study was carried out from January 2017 to December 2017 for a period of one year. Subjects were enrolled from Enam Medical College and Hospital. Patients diagnosed as bronchial asthma were taken as group A and healthy individuals were as a group B. The asthmatic patients were divided into groups those having chronic stable bronchial asthma and those having acute severe asthma. Results: Serum Mg++ level was significantly (p=0.000) lower in asthmatic patients 1.59±0.24 as compared with healthy controls (2.05±0.34) and significantly lower (p=0.006) in asthmatic patients during exacerbation (1.49±0.27) when compared to stable asthmatics (1.69±0.15). Asthmatic on ≥3 drugs has significantly (p=0.000) lower serum Mg++ 1.43±0.23 than those on <3 drugs (1.65±0.22). Conclusions: Serum Mg++ level was significantly lower in asthmatic patients during exacerbations compared with stable asthmatics. Journal of National Institute of Neurosciences Bangladesh, 2019;5(1): 38-41